Supporting Flipped and Gamified Learning With Augmented Reality in Higher Education - Lu, Angel; Wong, Crusher S. K.; Cheung, Richard Y. H.; Im, Tarloff S. W. (Frontiers in Education, 2021)
Chemistry education is challenging when many students cannot see the relevance and interest between what they learn at school and their everyday life outside the curriculum. Due to the prevalence of chemicals in real life, students lose interest in those not-so-novel Chemistry problems as they are satisfied with their rudimentary grasp of knowledge. Therefore, it is of paramount importance to draw students’ attention to those day-to-day Chemistry concepts, a task in which augmented reality (AR) can be a competent pedagogical facilitator. Despite its popularity due to the development of smart devices, educators are still averse to adopting AR in teaching because of the doubts about its pedagogical effectiveness and difficulties in implementation. This paper will demonstrate an AR app developed by City University of Hong Kong (CityU) for a year four undergraduate Chemistry course under two UGC’s project funds and CityU’s Teaching Development Grant that aligns with the university’s Discovery and Innovation-enriched Curriculum. The learning theories and technology stack of development and deployment will be shared in this paper. The consideration during preparation, production, and publishing will also be documented. A pilot survey about students’ perception of the AR showed positive feedback for the AR app in terms of enhancing awareness, learning, understanding, and engagement, which addresses the concerns of retaining students’ engagement during teaching and learning real-life Chemistry. We hope that educators who are interested in adopting AR can gain insights from this AR development experience. This research can act as a foundation for further exploration of applying AR in secondary and tertiary Chemistry education.